2022
DOI: 10.14710/jmki.10.3.2022.260-270
|View full text |Cite
|
Sign up to set email alerts
|

Health Information System Krama Bali Sejahtera Public Services Innovation Improves Denpasar Community's Trust For Healthy Behavior Through Adaptation Of New Habits

Abstract: The government in providing public services to the community is required to be effective and efficient, therefore it is continuously expected to be able to innovate services in a better direction to improve quality. Service quality is an important thing that determines public trust in public services to be able to realize community participation by increasing knowledge, trust and developing community habits regarding the concept of healthy behavior in adopting new habits and closer government relations with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The results of previous research revealed that public service innovation dominated by local governments rather than the central government [22], [25], because the coverage of services at the regional level is more varied and specific [22], and generally carried out by local governments spread across the island of Java [25], [27]. Based on government policy, public service innovation is prioritized in the health sector [28]. This is caused by conditions that demand health to be the world's top priority in the last 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…The results of previous research revealed that public service innovation dominated by local governments rather than the central government [22], [25], because the coverage of services at the regional level is more varied and specific [22], and generally carried out by local governments spread across the island of Java [25], [27]. Based on government policy, public service innovation is prioritized in the health sector [28]. This is caused by conditions that demand health to be the world's top priority in the last 4 years.…”
Section: Resultsmentioning
confidence: 99%